Sericin and Pineapple Fruit Extract as Natural Agents Inhibiting Browning and Improving Antioxidant Activity in Fresh-cut Ripe Mangoes cv. Nam Dok Mai - Mathurot Kumthongwathana; Suriyan Supapvanich; Nutthachai Pongprasert; Chalermchai Wongs-Aree; Panida Boonyaritthongchai (My University, 2024)
Recently, the use of natural agents to improve quality has attracted a lot of attention on fresh-cut produce and minimally processed fruit. The aims of this work were to investigate the efficiency of sericin and fresh pineapple juice (selected natural agents) on browning inhibition and antioxidant activity of fresh-cut ‘Nam Dok Mai’ mangoes during refrigeration (4°C). Based on a preliminary study and our previous work, 2% sericin (S) and 50% pineapple juice (PJ) were selected. Biological parameters related to enzymatic browning incidence, antioxidants and antioxidant enzyme activity of the fresh-cut mangoes immersed in 2% S, 50% PJ and 50% PJ incorporated with 2% S (PJ+S) were investigated. Immersion in S, PJ or PJ+S inhibited enzymatic browning due to delaying of discoloration, lowering of browning index (BI) and increases in polyphenol oxidase (PPO) and peroxidase (POD) activities compared to control treatment. The lowest PPO and POD activities and total phenolic content were found in the S treated fresh-cut mangoes. PJ+S treated fresh-cut mangoes had antioxidant activities higher than other treatment. All treatments enhanced the activities of antioxidant enzymes, especially PJ immersion. Therefore, S and PJ show potential as natural agents that can inhibit browning and improve antioxidant activity in fresh-cut mangoes during refrigeration.
Keywords: Browning; Sericin; Pineapple and bromelain studies